2017
DOI: 10.5709/acp-0210-1
|View full text |Cite
|
Sign up to set email alerts
|

Exploring Modality Compatibility in the Response-Effect Compatibility Paradigm

Abstract: According to ideomotor theory, action planning is based on anticipatory perceptual representations of action-effects. This aspect of action control has been investigated in studies using the response-effect compatibility (REC) paradigm, in which responses have been shown to be facilitated if ensuing perceptual effects share codes with the response based on dimensional overlap (i.e., REC). Additionally, according to the notion of ideomotor compatibility, certain response-effect (R-E) mappings will be stronger t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 45 publications
(84 reference statements)
1
7
0
Order By: Relevance
“…According to the common logic of dimensional overlap, stimulus features prime actions with compatible features ( element-level compatibility ; Kornblum, Hasbroucq, & Osman, 1990; Proctor & Reeve, 1990). Following ideomotor theory, such priming should also occur for features of anticipated effects, and this is precisely what studies have reported (see also Ansorge, 2002; Badets, Pesenti, & Olivier, 2010; Chen & Proctor, 2013; Földes, Philipp, Badets, & Koch, 2017; Kunde, 2003; Pfister, Janczyk, Wirth, Dignath, & Kunde, 2014; Yamaguchi & Proctor, 2011; Zwosta, Ruge, & Wolfensteller, 2013).…”
Section: Empirical Approaches To Ideomotor Action Controlsupporting
confidence: 74%
“…According to the common logic of dimensional overlap, stimulus features prime actions with compatible features ( element-level compatibility ; Kornblum, Hasbroucq, & Osman, 1990; Proctor & Reeve, 1990). Following ideomotor theory, such priming should also occur for features of anticipated effects, and this is precisely what studies have reported (see also Ansorge, 2002; Badets, Pesenti, & Olivier, 2010; Chen & Proctor, 2013; Földes, Philipp, Badets, & Koch, 2017; Kunde, 2003; Pfister, Janczyk, Wirth, Dignath, & Kunde, 2014; Yamaguchi & Proctor, 2011; Zwosta, Ruge, & Wolfensteller, 2013).…”
Section: Empirical Approaches To Ideomotor Action Controlsupporting
confidence: 74%
“…1), verbal overlap (Koch & Kunde, 2002; Paelecke & Kunde, 2007, Exp. 2; for a similar REC effect using verbal responses, see also Badets, Koch, & Toussaint, 2013; Földes, Philipp, Badets, & Koch, 2017), overlap in the duration of key presses and of the effects (Kunde, 2003), and overlap in rotation directions of actions and effects (Janczyk, Yamaguchi, Proctor, & Pfister, 2015). Further, effects applied to the actor’s body appear to behave similar to those occurring in the environment (Pfister, Janczyk, Gressmann, Fournier, & Kunde, 2014; Wirth, Pfister, Brandes, & Kunde, 2016).…”
Section: The Rec Effectmentioning
confidence: 94%
“…In another study that only showed spatial effects, the difference between the short and long delay was relatively small (short delay = 300 ms, long delay = 400 ms) compared to other temporal manipulations (50 ms vs. 2000 ms or 50 ms vs. 1200 ms) (Pfister et al, 2017 ). Furthermore, previous observations of auditory pitch-based spatial action–effect compatibility point to a possible role of modality-specific processes in effect anticipation (Földes et al, 2017 ). Further research is needed to explain why action effect features may be retrieved independently, and under which circumstances.…”
Section: Discussionmentioning
confidence: 86%